Sosialisasi dan Pelatihan Pengembangan Pupuk Organik Berbasis Tanaman Pangan yang Ramah Lingkungan di Desa Barangmamase, Kecamatan Galesong Selatan Kabupaten Takalar - Andi Amran Asriadi; Firmansyah Firmansyah; Nailah Husain (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Barangmamase Village, Galesong Selatan District, Takalar Regency is a village where most of the population relies on the economy from the agricultural sector. However, in the implementation of agriculture, this village has not utilized natural products, in this case cow dung waste, as the basic material for organic fertilizer used in its own agriculture and other wastes. So that this community service aims to make the Barangmamase Village community able to make solid and liquid organic fertilizers made from compost waste made from cow dung, as well as banana peel waste to improve agriculture and the community's economy. Therefore, in PKM activities, the implementing team provides socialization and training on the development of organic fertilizers as information on public awareness of the impact of soil fertility, inorganic fertilizers on the environment and health, as well as the level of fertilizer prices at the farmer level which tends to be high and with availability levels that are often scarce in the community. Based on the results of organic farming development activities and/or the use of organic materials and fertilizers on plants, it can reduce household waste and increase plant fertility in the community.